PANDANGAN ISLAM TERHADAP PENGENTASAN PELACUR MELALUI METODE BERPIKIR OPTIMIS - Tri Yuliana Wijayanti (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Islam views prostitution as dirty acts and adultery whose perpetrators must return the consideration of whipping or stoning. Prostitution is a very destructive classic problem, but in its response it is often hampered by indifference, despair, and depression in prostitutes. Therefore the Ministry of Social Affairs through the rehabilitation system in addition to providing skills also emphasizes an optimistic mindset. This article in the literature study discusses why Islam views the eradication of prostitutes through the method of optimistic thinking. The conclusion that can be drawn from Islam is the religion of Grace which denounces the attitude of despair and asks for optimism in order to always receive guidance, help, and thank God.